Characterization of trace elements and radionuclides and their risk assessment in red mud - ARTIR, RECEP (ELSEVIER SCIENCE INC, 2008)
Red mud is a waste and tail material from primary aluminum production, and is named for its color, coming from its iron oxide content. The quantity of red mud is almost equal to the primary aluminum production and leads to a considerable environmental issue. Red mud of the ETI Seydisehir Aluminum Plant is considered as detrimental waste for storage due to its content of various metal oxides, elements and caustics. This detrimental effect is classified into two groups: first, environmental health and second, the cost of storage. In order to minimize the negative effect of red mud, there have been or are presently many investigations carried out on usage of red mud in building materials. However, no effective way of utilizing red mud has yet been found. in this study domestic red mud was investigated and chemical analyses were performed by EDAX and XRF techniques. Radioactivity of the samples was also measured with gamma spectroscopy. The concentrations of elemental Na, Al, Si, Ca, Ti, Fe, S and K were determined by EDAX and XRF. In addition, Cr, Zr, Sr, Ni and Y were also identified as impurities. According to gamma spectroscopy results radium, uranium, thorium and potassium were determined as radioactive elements. It was observed that the amounts of the radioactive elements present in the red mud are within safe limits. Therefore, if domestic red mud originated from Seydisehir could be utilized as reinforcement material in composites, and in building materials, it can be considered safe in terms of environmental and human health. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: red mud; radioactivity; radionuclides; gamma radiation; risk assessment; THERMAL-BEHAVIOR